2017
DOI: 10.1016/j.trci.2017.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Technology for home dementia care: A prototype locating system put to the test

Abstract: IntroductionThe user experience of persons with dementia and their primary caregivers with locating systems is not firmly established.MethodsEighteen dyads used a prototype locating system during 4 weeks. Primary outcome measures were ratings of usability, and product functions and features. Secondary outcome measures were caregiver burden, perceived self-efficacy, frequency of use, and willingness to purchase the prototype. Changes in scores between baseline (T1) and end of testing period (T2) were compared b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(55 citation statements)
references
References 24 publications
2
53
0
Order By: Relevance
“…Although the selected products were similar, usability ratings by dyads of product B were significantly better than ratings of product A throughout the study. Differences in ratings of usability and design features within dyads are in line with previous studies, which have suggested that the needs and preferences of PwDs and CGs with GPS devices need to be taken into consideration as they may differ [7,8,42,43]. Also, the finding that usability ratings with both products decreased after 4 weeks of use, but not significantly, seems to imply that users' expectations could not be fully met, but that they were not entirely dissatisfied.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Although the selected products were similar, usability ratings by dyads of product B were significantly better than ratings of product A throughout the study. Differences in ratings of usability and design features within dyads are in line with previous studies, which have suggested that the needs and preferences of PwDs and CGs with GPS devices need to be taken into consideration as they may differ [7,8,42,43]. Also, the finding that usability ratings with both products decreased after 4 weeks of use, but not significantly, seems to imply that users' expectations could not be fully met, but that they were not entirely dissatisfied.…”
Section: Discussionsupporting
confidence: 87%
“…To date, studies on prototype and commercial GPS devices in dementia care have used different product types with similar functions and design features. Typically, products are small (e.g., pager sized or watch sized), discrete or nonvisible (e.g., worn around the waist, neck, wrist, or placed inside a pocket or shoe sole), have two to six main functions (e.g., location, telephone, geofencing, alarm, fall detection, and speed alert), no buttons (i.e., passive systems) or one to three buttons (i.e., active systems), and are lightweight [5] , [6] , [7] , [8] , [9] , [10] , [11] . These functions and features are in line with most expert recommendations [7] , [12] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(27) Despite the caregivers' preparation to manage the technologies, many indicate difficulty to implement them on a daily basis, mainly due to the flaws they present, which reinforces the need for system improvements. (28) Regarding the use of robotic navigation aids, the findings support the assertion that they effectively support the orientation and movement of demented people and are able to reduce the task performance time. Nevertheless, as the study included in the SLR associated the use of the robotic navigation aid with verbal direction prompts, the effectiveness of the contextual navigation prompts or not was questioned, as this was not evaluated separately in the research.…”
Section: Articlessupporting
confidence: 53%
“…In experimental work of [13], the location tracking system based on telemetry is proposed where GPS receiver is worn by patient and family member or caregiver could call and able to view location of wearer on map showed on CRT. The variety of location tracking solutions are offered and few studies are conducted to evaluate effectiveness of offered solutions such as in work [14], prototype is created and evaluated for improving care for dementia. A mobile app with prime functions such as locate, call, alarm, service hotline and two secondary functions such as zone mapping and zone sharing served as locating system.…”
Section: Review Of Related Workmentioning
confidence: 99%